Implementasi Instagram Dalam Peningkatan Penjualan Properti Di PT. Adong Kartika Jaya - Novianto, Gigih Dwi; Widodo, Teguh (Institut Teknologi dan Sains Mandala, 2024)
Sales are an important aspect to be considered by every business manager, including property entrepreneurs. In the digital era like today, one effective method in increasing property sales is through the use of social media such as Instagram. One property company that utilizes Instagram in its sales is PT Adong Kartika Jaya. Adong Kartika Jaya is one of the property developers with considerable experience in Malang City. The purpose of this study is to determine the implementation of Instagram in increasing property sales at PT Adong Kartika Jaya. This study uses a qualitative method, with data collection techniques including direct observation, literature review, and direct interviews with marketing team members and Instagram administrators at PT Adong Kartika Jaya. The results of this study show that the utilization of Instagram as a means to increase sales has a direct economic impact on PT Adong Kartika Jaya, including increased sales and revenue. In addition, the induced economic impact includes increased income. The implementation of Instagram as a promotional tool also influences increased sales through expanding business reach and sales volume.